First record of the invasive alien species Cynaeus angustus (LeConte, 1851) (Coleoptera, Tenebrionidae) in Bulgaria - Ognyan Sivilov; Hristina Hristova (Historia naturalis bulgarica, 2022)
The invasive alien species Cynaeus angustus (LeConte, 1851) was detected for the first time in Bulgaria. In 2020-2022, eight exemplars of this North American pest were collected at three sites along the Danube River. Its distribution, microhabitat affinity, food preferences as well as some methods for control are outlined. Photographs of the adult habitus, male genitalia and female ovipositor are also provided.